Persepsi Body Image Pekerja Di Kota Jayapura - Elisabet Bre Boli; Oktliana Pasangka (STIKES Columbia Asia Medan, 2025)
Appearance is one of the important factors for humans in living their lives. However, each individual's perception of their own body tends to be inconsistent with the good anthropometric body standards. This body image perception is closely related to lifestyle, diet, physical activity, and environment. This study aims to explore the body image perception of workers in Jayapura City. This research is an exploratory study to gain an in-depth understanding of the body image perception of workers in Jayapura City. The subjects of this study were 379 workers domiciled in Jayapura City. Data was collected using a body image perception questionnaire and anthropometric measurements were conducted on the workers. The results showed that 53% of respondents were female, 60% were in the early working-age category, and 47% worked as civil servants, military personnel, police officers, or employees of state-owned enterprises. Furthermore, most respondents had normal nutritional status (60%) and 87% had a negative body image perception. Cross-tabulation analysis found that a positive body image perception was mostly found among respondents with normal nutritional status. However, many respondents with normal nutritional status still had a negative body image perception. Further studies are needed to investigate the factors related to body image perception to develop interventions that improve workers' understanding of the ideal body shape.